2001
DOI: 10.3748/wjg.7.5.685
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection of human hepatoma cell line 7721 in vitro

Abstract: AIM To establish a cell culture system with long-term replication of hepatitis C virus in vitro.METHODS Human hepatoma cell line 7721 was tested for its susceptibility to HCV by incubating with a serum from a patient with chronic hepatitis C. Cells and supernatant were harvested at various phases during the culturing periods. The presence of HCV RNA, the expression of HCV antigens in cells and/or supernatant were examined by RT-PCR, in situ hybridization and immunohisto-chemistry respectively. RESULTSThe intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Further, the use of RT-PCR for detection of viral RNA in these studies could not rigorously rule out possible contamination by the virus from the serum. Several laboratories have also shown that HCV can infect B-cell (30), T-cell (18,32,39), and hepatoma cell (14,41) lines in culture, but the infection is usually transient and inefficient. Nevertheless, these studies suggested that B or T cells could support HCV replication, albeit inefficiently, at least in vitro.…”
mentioning
confidence: 99%
“…Further, the use of RT-PCR for detection of viral RNA in these studies could not rigorously rule out possible contamination by the virus from the serum. Several laboratories have also shown that HCV can infect B-cell (30), T-cell (18,32,39), and hepatoma cell (14,41) lines in culture, but the infection is usually transient and inefficient. Nevertheless, these studies suggested that B or T cells could support HCV replication, albeit inefficiently, at least in vitro.…”
mentioning
confidence: 99%
“…Infected Huh7.5 cells were able to shed virus into culture medium, where the later could efficiently infect naïve Huh7.5 cells (results not shown). Infection of cells in vitro with HCV from a variety of sources can at least demonstrate the infectivity of the virus making these systems useful in evaluating drugs for antiviral activity or inhibition of HCV replication [19,22,32]. Transfection with synthetic full-length or near-full-length HCV RNA has the drawback that the RNA used for transfection is homogenously synthesized containing well defined sequence whereas in cases of natural infection with the whole viral particles several quasispecies of different magnitudes of infectivity could be coexisting, thus mimicking the in vivo infections of HCV.…”
Section: Discussionmentioning
confidence: 99%
“…Huh7.5 cells were used for HCV infection experiments and assessment of viral replication. Huh7.50 cells were cultured and infected with HCV particles according to protocols described by Seipp et al, [21] and Song et al,[22]. Assessment of the successful viral infection in Huh7.5 cells throughout the culture duration was confirmed at the transcriptional level by Reverse Transcription Polymerase Chain Reaction (RT-PCR) amplification of HCV RNA and at the translational level by SDS-PAGE of cell lysates followed by Western blotting to determine the de novo synthesis of non structural proteins e.g NS5A.…”
Section: Methodsmentioning
confidence: 99%
“…HCV RNA is detected for at least three months following infection. This result also suggested that if the HCV-infected hepatoma cells were co culture with PBMCs, they were able to transfer the virus into PBMCs [16]. …”
Section: Hcv Infection Systemmentioning
confidence: 99%